Do consumers prefer multidimensional or multiple single-issue sustainability labels? Evidence from rice markets in Germany and Singapore - Checco, Julia; Demont, Matty; Coote, Leonard V.; Schulze, Maureen; Permani, Risti; Nuraeni Muflikh, Yanti; Mitchell, Jaquie; Aziz, Ammar Abdul (Elsevier BV, 2025)
Multidimensional labels have emerged as a potential solution to the proliferation of multi-labelling in the food industry, which often leads to consumer confusion and scepticism. This study examines the performance of the Sustainable Rice Platform (SRP) multidimensional label compared to single-issue labels (Organic, Fairtrade, and World Wildlife Fund) and origin attributes in the rice market. We assessed SRP’s potential to replace or complement existing labelling systems using a discrete choice experiment with 507 German and 361 Singaporean rice consumers, measuring willingness to pay for rice with different label combinations. Results indicate that while SRP’s familiarity and trust lagged most established single-issue labels in both markets, its performance varied by market context. In Singapore’s unsaturated label market, SRP outperformed single-issue labels and origin, whereas in Germany’s saturated market, familiar labels like Fairtrade, Organic or EU origin surpassed SRP. Partial substitution effects occurred when SRP was combined with Organic in both markets, but SRP cannot fully replace the Organic label. Complementary effects emerged when SRP was combined with trustworthy singleissue labels or favourable origin labels. Importantly, multi-labelling with Organic, Fairtrade and WWF labels outperformed the SRP label by almost double in Singapore and triple in Germany, suggesting consumers value multiple simple certifications over a single, complex multidimensional label. These findings contribute to existing literature on multidimensional and multi-labelling scheme effectiveness, revealing market-specific consumer preferences. The results have significant implications for sustainable labelling strategies in the rice industry and can guide policymakers and food companies in developing more effective sustainability communication approaches.